24-hydroxycholesterol moderates the effects of amyloid-β on expression of HMG-CoA reductase and ABCA1 proteins in mouse astrocytes - Zahra Nazeri; Ghorban Mohammadzadeh; Mojtaba Rashidi; Shirin Azizdoost; Maryam Cheraghzadeh; Alireza Kheirollah (Advanced Biomedical Research, 2023)
Background: Elevated brain cholesterol increases the risk of Alzheimer's disease. Production of 24-hydroxycholesterol (24s-OHC) by neurons prevents cholesterol accumulation in the brain. In this study, we investigated the effect of 24s-OHC on the HMG-COA reductase and ABCA1 which are involved in the brain cholesterol homeostasis with or without β-amyloid in astrocytes. Methods and Materials: Astrocytes were treated with 24s-OHC with or without Aβ. Western blot and real-time polymerase chain reaction were done to detect protein and gene expression of β-hydroxy-3-methyl-glutaryl-coenzyme A reductase (HMGCR) and ABCA1, respectively. Cholesterol release was determined using a quantitation kit. Results: Protein levels of HMGCR and ABCA1 were significantly increased by Aβ; however, the 24s-OHC was able to restore their levels and diminish the effect of amyloid-β. Aβ did not have a significant effect on HMGCR expression, while 24s-OHC reduced it by 68%. Aβ-induced ABCA1 expression did not increase cholesterol efflux as the lower levels of cholesterol in conditioned medium of Aβ-treated cells were found. Conclusion: Our novel findings show that Aβ affects two key elements in the brain cholesterol homeostasis, HMGCR and ABCA1, which are crucial in cholesterol synthesis and efflux. Since 24s-OHC could suppress the Aβ effects on enhancement of HMGCR and ABCA1, therefore the cytochrome P450 46A1 (Cyp46A1), which is exclusively expressed in the central nervous system and responsible for producing of 24s-OHC, could consider as a therapeutic target in the cholesterol-related neurodegenerative diseases such as Alzheimer's disease.